Analysis of Environmental Problem-Solving Ability of Students In Class XI Social Science at State Senior High School 17 West Jakarta - Fellix Rimba; Ranny Rastati (Malaysia) (Tunas Geografi, 2023)
The environment is an important pillar for all life, including human life. However, today's environmental problems cannot be separated from human activities. It is necessary to have environmental problem-solving skills in students. This study aimed to analyze the environmental problem-solving ability of students in Class XI Social Science at State Senior High School 17 West Jakarta. The research method used is descriptive quantitative. This study used a sample of 27 students. The sampling technique used is simple random sampling. Research results showed that the ability to solve environmental problems for class XI Social Science at State Senior High School 17 West Jakarta was classified as high (71,22%). The results of the indicator research are as follows: defining the problem using test questions at 30,19% and questionnaire results at 31,02%, identifying problems using test questions at 25,19% and questionnaire results at 21,27%, formulating various alternative solutions using test questions at 23,52% and questionnaire results of 25,19% and determine the best solution using test questions of 21,10% and questionnaire results of 22,52%. The highest score is found on the indicator defining the problem, and the lowest score on determining the best solution. This finding implies that there is a tendency for students to understand, identify and formulate solutions to environmental problems.Keywords: Ability, Problem-Solving, Environmental, Senior High School